2001
DOI: 10.1029/2000ja900156
|View full text |Cite
|
Sign up to set email alerts
|

Substorm dependence of chorus amplitudes: Implications for the acceleration of electrons to relativistic energies

Abstract: Abstract.Intense interest currently exists in determining the roles played by various wave-particle interactions in the acceleration of electrons to relativistic energies during/following geomagnetic storms. Here we present a survey of wave data from the CRRES Plasma Wave Experiment for lower band (0.1-0.5fce) and upper band (0.5-1.0fce) chorus, fce being the electron gyrofrequency, to assess

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
637
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 481 publications
(696 citation statements)
references
References 29 publications
58
637
1
Order By: Relevance
“…There are discrepancies of the required wave amplitudes between 50 and 100 eV/nT (less than a factor of 2), and some of these discrepancies are due to the ambiguity of the assumed wave normal angle and the plasma parameters. The mean value of the required wave amplitudes at 50 and 100 eV/nT electrons are 7.48, 9.06, 12.0, 13.7, and 14.9 pT for Kp = 0, 1, 2, 3, and 4, respectively, while the observed average wave amplitudes of the chorus waves are a few pT during quiet conditions and enhanced during active conditions with amplitudes of^10 pT [Meredith et al, 2001]. Therefore, the required wave amplitudes are roughly consistent with the observed average amplitudes of the chorus waves.…”
Section: Electron Loss Time Scalementioning
confidence: 98%
See 1 more Smart Citation
“…There are discrepancies of the required wave amplitudes between 50 and 100 eV/nT (less than a factor of 2), and some of these discrepancies are due to the ambiguity of the assumed wave normal angle and the plasma parameters. The mean value of the required wave amplitudes at 50 and 100 eV/nT electrons are 7.48, 9.06, 12.0, 13.7, and 14.9 pT for Kp = 0, 1, 2, 3, and 4, respectively, while the observed average wave amplitudes of the chorus waves are a few pT during quiet conditions and enhanced during active conditions with amplitudes of^10 pT [Meredith et al, 2001]. Therefore, the required wave amplitudes are roughly consistent with the observed average amplitudes of the chorus waves.…”
Section: Electron Loss Time Scalementioning
confidence: 98%
“…The chorus waves are frequently observed from the nightside through dawn to the dayside equatorial magnetosphere [e.g., Meredith et al, 2001;Li et al, 2009]. Therefore, the chorus wave is a primary candidate that interacts with plasma sheet electrons in the morning sector and causes them to precipitate into the atmosphere.…”
Section: Evaluation Of Theoretical Loss Time Scales Based On Pitch Anmentioning
confidence: 99%
“…[17] Whistler-mode chorus waves, which are observed in the low-density region outside of the plasmapause, can fall into the frequency range between 0.1 and 5 kHz [e.g., Meredith et al, 2001]. In order to exclude these emissions from the study we adopt a criterion based on the amplitude of the waves in the band f ce < f < 2f ce .…”
Section: Identification Of Plasmaspheric Hiss and Lightning Generatedmentioning
confidence: 99%
“…The pitch-angle scattering of the radiation belt energetic electrons by chorus can lead to significant precipitation into the atmosphere [Lorentzen et al, 2001;Meredith et al, 2001;Summers, 2005]. Tsurutani and Smith [1974] and Anderson and Maeda [1977] found that the onset of the chorus emissions coincided with the injection of substorm electrons with energies of ∼10-100 keV.…”
Section: Introductionmentioning
confidence: 99%